The green and sustainable care facilities of elderly care home: An exploratory study of rumah seri kenangan cheras, Selangor - Hasbollah, Hasif Rafidee; Yusof, Nazaruddin; Mohd Nawi, Mohd Nasrun (2018)
The terminologies of “Green Building” and “Sustainable Building” explore the practice of creating structures by using processes that are environmentally responsible and resource efficient. This is done through examining a building's life-cycle that is related with economy, utility, durability, and comfort of occupants. In Malaysia, “Green Building” and “Sustainable Building” for Care Facilities of Elderly Care Homes are still in its infancy. Elderly Care Home is a long term care facility that provides permanent living space and support for the elderly, with the activities of daily living that offers personal care and support. This research explores the Green and Sustainable Care Facilities of Elderly Care Home-Rumah Seri Kenangan (RSK) in Cheras, Selangor (GSch-RSK). RSK is established to provide care, treatment and shelter to the elderly poor, aged 60 years and above. It provides care and protection services; guidance and counselling; recreational activities; medical treatment; occupational therapy; and physiotherapy for the elderly to live in peace and enjoy a good quality of life. This research adopts observation, interview, and document review methods in gathering data. The findings indicate six characteristics of GSch-RSK which consists of (1) Location and Surrounding area of RSK which is explored and consisted of road, RSK building and green landscape; (2) Integrated Operation of Operations and Maintenance in daily cleaning and monthly elevator maintenance; (3) Healthy Environment of Atmosphere and Well-being that consist of bright colours and ventilation system (modern windows and exhaust fan); (4) Waste Management System that includes garbage removal and designated sewerage; (5) Energy Efficiency characteristic that is the installation of the Energy Efficiency Appliances and Solar Panel System; and (6) Sustainable and Green Management of Green Landscape which has been practiced by setting up Rain Garden and planting Edible Green leaves and flowers. All these characteristics are vital in developing the theoretical framework of Green and Sustainable Care Facilities of Elderly Care Homes in Malaysia. Finally, these characteristics will be used for the development framework of existing buildings of Elderly Care Homes in Malaysia.